Analysis of a 17.9 kb region from Saccharomyces cerevisiae chromosome VII reveals the presence of eight open reading frames, including BRF1 (TFIIIB70) and GCN5 genes - Feroli, Fiorella (2014)
We report the nucleotide sequence of a 17,893 bp DNA segment from the right arm of Saccharomyces cerevisiae chromosome VII. This fragment begins at 482 kb from the centromere. The sequence includes the BRF1 gene, encoding TFIIIB70, the 5' portion of the GCN5 gene, an open reading frame (ORF) previously identified as ORF MGA1, whose translation product shows similarity to heat-shock transcription factors and five new ORFs. Among these, YGR250 encodes a polypeptide that harbours a domain present in several polyA binding proteins. YGR245 is similar to a putative Schizosaccharomyces pombe gene, YGR248 shows significant similarity with three ORFs of S. cerevisiae situated on different chromosomes, while the remaining two ORFs, YGR247 and YGR251, do not show significant similarity to sequences present in databases.